Alopecia Areata (Indralupta): A successfully treated case with Ayurvedic Management. - Ahirwar, Pramendra; Fiaz, Shamsa (International Research Journal of Ayurveda & Yoga, 2024)
Alopecia areata1, an autoimmune disease characterised by patchy hair loss can be correlated with Indralupta in Ayurveda text Indralupta can be compared to Alopecia based on its signs and symptoms.ALOPECIAis one of the most emerging diseases of the 21 century mainly due to changed life style westernized culture, junk food habits & race for cosmetics. It is more prevalent in young people below 20 years but children and adults of any age group may also be affected. This disease poses a huge financial and psychological burden for the patients and his family. Even though medical science has advanced to a great extent in the field of cosmetology and trichology, but still there is no definite cure for the present condition. Treatment options include topical and systemic steroids, topical irritants & immunotherapy which creates an allergic reaction with the production of T-suppresser cells which inhibits an auto immune reaction. Expensive lotions, oils & shampoos are available in the market but without any promising results.. Due to the side effects and limitation of the contemporary science, effective and harmless treatment/procedure is expected from Alternative medical sciences. Ayurveda has great potential to treat such autoimmune diseases. A study is planned for evolving an efficient and cost effective remedy which may prove to be a boon for Indralupta patients. In this regard, Ayurveda advocates Prachhana karma3 which is a localized therapy which stimulates hair follicles, improves blood circulation and hence promotes re growth. In order to enhance this action further a medicated paste of Madhukadi lepa4is applied topically which is Keshya and thereby promotes hair growth. It is also proposed to evaluate the efficacy of only Madhukadi lepa without Prachhana karma in Indralupta to see if it is effective alone in combating Indralupta. Madhukadi lepa contains Yashtimadhu,Nilkamal, Moorva,Bhringaraj, Tila tailam, Gritha and Go-dugdha. Keeping in mind the systemic involment in present condition, Bhringrajadi rasayan5is also selected which is considered to be the best Rasayana for hair disorders and contains Bhringaraj, Amalaki, and Tila which provides, nutrition and hair growth Here a case of Indraluptawhich is successfully treated with Prachhan karma , Shirolepa and Bhringarajadi Rasayana.